2023
DOI: 10.1136/jnnp-2022-330192
|View full text |Cite
|
Sign up to set email alerts
|

Functional neurological disorder is a feminist issue

Abstract: Functional neurological disorder (FND) is a common and disabling disorder, often misunderstood by clinicians. Although viewed sceptically by some, FND is a diagnosis that can be made accurately, based on positive clinical signs, with clinical features that have remained stable for over 100 years. Despite some progress in the last decade, people with FND continue to suffer subtle and overt forms of discrimination by clinicians, researchers and the public. There is abundant evidence that disorders perceived as p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 96 publications
(194 reference statements)
0
1
0
1
Order By: Relevance
“…Raynor and Baslet described the historical understanding over the FND etiologies and highlighted that these heterogenic premises, as well as the variable response to treatments, could suggest that FNDs are in fact complex disorders of which clear etiology could be more related to the individual than to a pathological redundant pattern [60]. In some cases, as the diagnosis of FND could be the subject of inconsistencies and discrimination [61], efforts are currently made to diminish them. In this way, Mark [62] suggested that a major source of unfavorable response (in the patient-provider relationship) could be historical biases, while McLoughlin et al [61] pointed out that FND could be considered as a feminist issue fueled not only by historical aspects, but also by contemporary perspectives.…”
Section: Mechanisms and Predisposing Factors For Functional Neurologi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Raynor and Baslet described the historical understanding over the FND etiologies and highlighted that these heterogenic premises, as well as the variable response to treatments, could suggest that FNDs are in fact complex disorders of which clear etiology could be more related to the individual than to a pathological redundant pattern [60]. In some cases, as the diagnosis of FND could be the subject of inconsistencies and discrimination [61], efforts are currently made to diminish them. In this way, Mark [62] suggested that a major source of unfavorable response (in the patient-provider relationship) could be historical biases, while McLoughlin et al [61] pointed out that FND could be considered as a feminist issue fueled not only by historical aspects, but also by contemporary perspectives.…”
Section: Mechanisms and Predisposing Factors For Functional Neurologi...mentioning
confidence: 99%
“…In some cases, as the diagnosis of FND could be the subject of inconsistencies and discrimination [61], efforts are currently made to diminish them. In this way, Mark [62] suggested that a major source of unfavorable response (in the patient-provider relationship) could be historical biases, while McLoughlin et al [61] pointed out that FND could be considered as a feminist issue fueled not only by historical aspects, but also by contemporary perspectives.…”
Section: Mechanisms and Predisposing Factors For Functional Neurologi...mentioning
confidence: 99%
“…Allein schon die komplexen diagnostischen und therapeutischen Fragen, die sie klinisch aufwerfen können, tragen dazu bei, dass die erforderliche und grundsätzlich einen Erfolg versprechende Behandlung von FNS viel zu oft ausbleibt. Dazu kommt es trotz aller Fortschritte umso leichter, als an FNS leidende Menschen weiterhin subtilen und offenen Formen der Diskriminierung ausgesetzt sind, sei es durch Kliniker, Forscher und die Öffentlichkeit, und das rasch noch einmal mehr, wenn es sich um Frauen handelt 1 . Immer in Gefahr, ins „Niemandsland zwischen Neurologie und Psychiatrie“ 2 zu geraten, laufen FNS außerdem der überkommenen Organisation einer medizinischen Versorgung entgegen, in der die Trennung von somatischer und psychosozialer Medizin das Erkennen und Handeln im klinischen Alltag bestimmt.…”
Section: Introductionunclassified
“…A recent paper powerfully argues that this is a feminist issue. McLoughlin et al 4 start with the stark data on enduring gender bias and discrimination in medicineimplicit and explicitin terms of diagnostics, treatment and follow-up. This is matched by a lack of research, including women participants more generally and in what they label 'stereotypically female disorders' more specifically, echoing the broader global societal burdens faced by women, from violence through poverty to social exclusion.…”
mentioning
confidence: 99%